Evaluation of the lactic acid bacteria based formulated probiotic product for poultry - Al-Surrayai, T.; Al-Khalaifah, H.; Al-Mansour, H.; Kishk, M.; Al-Mutairi, A.; Sultan, H.; Al-Saleem, H. (Frontiers in Animal Science, 2022)
This study evaluated the effectiveness of a new probiotic product developed to reduce the effect of Salmonella infections and compared it to the efficacy of commercial probiotics in broiler chicken. Based on the in vitro assessment of the growth characteristics and safety to human health, four bacterial isolates were isolated, characterized, and identified as excellent candidates for the development of commercial probiotic feed additives for poultry. Compatibility and interactions among the four selected strains were investigated. After that, a preliminary study was conducted in which the selected isolates were evaluated individually in vivo with three different methods of application (water, feed, and oral gavage). The cycle included N = 312 chicks, which were divided into 13 groups, including control, distributed into four batteries, with 78 broiler chickens in each battery. There were eight replicates with 24 chicks in each replicate, and the analysis was randomly done in triplicate. The intentional parameters were growth performance, microbial analysis and humoral immune response. The results of the preliminary study assisted in formulating the new probiotic product. Then In vivo evaluations for the newly formulated product were performed with the comparison with two imported commercial products (Alterion and Galli pro fit) used in poultry farms in Kuwait. The second cycle included N = 96 chicks that were divided into four groups, including control. Each group has three replicates and each replicate has eight chicks, and the analysis was randomly done in triplicate. The results showed that although antibiotics were not used, all the growth parameters were similar and sometimes better than the control. The new product inhibited the growth of salmonella as a control and all chickens in different treatment gained a high mass of meat. The statistical analysis showed that no differences were observed in bird weight, weight gain, feed consumption, and feed efficiency between bacterial strains p>0.05. Also, the different probiotic treatments did not affect the total antibody IgM titers significantly in the broilers (P > 0.05). Thus, the newly formulated product was effective in reducing the salmonella.